IMPLEMENTATION OF BANK INDONESIA REGULATION NO. 18/40/PBI/2016 ON PAYMENT TRANSACTIONS USING CREDIT CARDS AT SHOPPING CENTERS IN BENGKULU CITY - Muhammad Tedy Dorisman Setiadi; Nur Sulistyo Budi Ambarini; Widiya N Rosari (Bengkoelen Justice : Jurnal Ilmu Hukum, 2020)
The objective of the research was to study the implementation of Bank Indonesia Regulation No.18/40 / PBI / 2016 onDouble Swipe of Credit Card. The empirical juridical approach method in this researchused primary and secondary data as the main research data, through interviews and literature. A credit card is a credit facility provided by the issuing bank to its customers for transaction. From the research it was found thatin prior to the enactment of Bank Indonesia Regulation No.18/40/PBI/2016 on Payment Transactions Using Credit Cards, there were merchants that still do double swipe on credit card during payment transactions, first in the EDC (Electronic Data Capture) machine and on the cash register machine. However,due to the restriction on double swipe on credit card, this had been reduced. It was also strengthened by a strict regulation in the form of sanctions, reprimands and threats of crime committed by Bank Indonesia to merchants who conduct double swipe on credit card. The mechanism of bank issuing the credit card in giving approval is always different, but the terms and procedures are relatively the same. Legal protection of credit card users occurs when the signing of credit card approval agreement between the issuing bank and users since there is not clear juridical regulation. The problem mostlyarisingregarding the credit cards usage was credit card data scam. The only way to prevent this was through the use of credit cards properly, securely store credit cards when making payment transactions using credit cards, and understand the procedure of using a credit cardinpayment transactions properly. In case of credit card violation, the holder must report to the bank issuing the credit card and Bank Indonesia.